1978
DOI: 10.4315/0362-028x-41.4.284
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Efficacy of a Potassium Sorbate Dip on Freshly Processed Poultry

Abstract: Fresh poultry breasts were dipped in a solution containing either 0, 2.5, 5.0 or 10.0% potassium sorbate for 1 min. Another lot of fresh poultry breasts was dipped in a suspension of either 103 or 105 cells of three strains of Salmonella/ml before being dipped in one of the potassium sorbate solutions. Use of a potassium sorbate dip significantly reduced the total number of viable bacteria on the poultry parts when compared to the untreated control parts after 7 days of storage at 10 C and after 8 days at 6 C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 0 publications
3
24
1
Order By: Relevance
“…These results agree with those reported by Robach and Ivey (1978), who observed oVodor in chicken breasts dipped in 2.5% sorbate two days later than in control legs. OV-odors were noticed by the panel members when the counts approached 9 log cfu/g.…”
Section: Resultssupporting
confidence: 96%
See 1 more Smart Citation
“…These results agree with those reported by Robach and Ivey (1978), who observed oVodor in chicken breasts dipped in 2.5% sorbate two days later than in control legs. OV-odors were noticed by the panel members when the counts approached 9 log cfu/g.…”
Section: Resultssupporting
confidence: 96%
“…Also Mendonca, Molins, Kraft, and Walker (1989) reported that 10% potassium sorbate solutions reduced the mesophiles and psycrotrophs counts in pork meat. Robach and Ivey (1978) reported that a 5% potassium sorbate dip signiWcantly reduced the total plate count of chicken and extended the shelf life of fresh poultry.…”
Section: Resultsmentioning
confidence: 99%
“…Similar pH values in KSP-and P-treated steaks, however, suggested that the antimicrobial activity of the KSP treatment in this study was not due to pH. Undissociated sorbic acid has been reported to have stronger antimicrobial properties than its potassium salt (Robach and Ivey, 1978;Robach and Sofos, 1982;Zamora and Zaritzky, 1987). On the other hand, the antimicrobial activity of potassium sorbate is known to increase as product pH approaches 4.75 and to decrease at pH values above 6-O-6.5 (Sofos and Busta, 1981;Eklund, 1983).…”
Section: Resultscontrasting
confidence: 58%
“…They reported BHA to be more effective against S. aureus than against E. coli and 400 ppm PG to have a strong lethal effect against E. coli. Robach et al (1977) found BHA inhibited Vibrio parahemolyticus at 50 ppm when used in trypticase soy broth and 400 ppm in a crab homogenate. Three strains of Clostridium perfringens were found to be inhibited by 150 ppm BHA in fluid thioglycollate medium (Klindworth et al 1979).…”
Section: Introductionmentioning
confidence: 98%
“…Robach (1979), working with trypticase soy broth at pH 6.0, found that 0.2% potassium sorbate was effective in delaying or inhibiting growth of Pseudomonas fluorescens and Pseudomonas putrefaciens. A 2.5% potassium sorbate dip was shown by Robach and Ivey (1978) to significantly reduce the total viable microorganisms on poultry parts held at 6OC and 10°C. An excellent review of the antimicrobial activity of sorbate was published by Sofos and Busta (1981).…”
Section: Introductionmentioning
confidence: 99%